Effect of a calibration aid and the intraoral scanner on the registration of a partially edentulous maxilla: an in vitro study - Boehm, Sophia; Rues, Stefan; Balzer, Alexandra; Rammelsberg, Peter; Waldecker, Moritz (The journal of prosthetic dentistry, 2025)
Statement of problem - Precise data are a prerequisite for accurately fitting restorations. Therefore, intraoral scanners have to be reliable. Data on differences between the same model of intraoral scanning systems are lacking. - Purpose - This in vitro study evaluated differences in the scanning accuracy of a partially edentulous maxilla between combinations of new intraoral scanners of a single model from the same manufacturer (Primescan; Dentsply Sirona) and several calibration aids. - Material and methods - The in vitro reference model simulated a maxilla with 6 prepared teeth for a complete arch fixed partial denture. Five precision ceramic balls were used to detect dimensional deviation between the reference model and the scan. Distances were divided into 4 categories, from short distances between 2 neighboring precision balls to the cross-arch distance with the scan path comprising all 5 balls. For each combination of 4 new intraoral scanners and their respective calibration aids, 12 model registrations were generated. The data were statistically analyzed using ANOVA (α=.05). - Results - Distance deviations increased with increasing scan path length and were significantly affected by the covariates “scanner” (P≤.023) and, for 3 of 4 distance categories, the “calibration aid” (short, medium, and long distances: P≤.013). For short and medium distances, acceptable scanning results were achieved for all test groups. The largest deviation was 539 µm for the cross-arch distance. - Conclusions - Scanning accuracy depends on the scanner and the calibration aid used, in particular, for spans exceeding a single quadrant.
Online veröffentlicht am 12. März 2024, Artikelversion: 20. Februar 2025
Gesehen am 28.07.2025